Globisporangium tabrizense sp. nov., Globisporangium mahabadense sp. nov., and Pythium bostanabadense sp. nov. (Oomycota), three new species from Iranian aquatic environments - Reza Ahadi; Ali Chenari Bouket; Alireza Alizadeh; Hossein Masigol; Hans-Peter Grossart (Scientific Reports)
Abstract During a survey on the biodiversity of oomycetes in aquatic environments in northwest Iran (East Azarbaijan and West Azarbaijan provinces), three Pythium and four Globisporangium isolates were recovered from agricultural water pools and irrigation canals, respectively. Through a polyphasic approach combining morphology and phylogenetic analysis using the nuclear rDNA ITS1-5.8 S-ITS2 (ITS) and partial sequences of the cytochrome c oxidase subunit I and II (COX1 and COX2), three novel species were identified namely Globisporangium tabrizense sp. nov., G. mahabadense sp. nov., and Pythium bostanabadense sp. nov. Furthermore, experiments confirmed the pathogenicity of all identified species on cucumber seedlings, suggesting a pathogenic lifestyle also in aquatic systems. Our research contributes to a better understanding of the diversity, host range and distribution of oomycetes genera Globisporangium and Pythium in northwestern Iran. Detailed morphological descriptions and illustrations are provided for all species.